Dose-response relationship between carotenoid intake and risk of depressive symptoms in postmenopausal women - Li, Xuexue; Wang, Su (Frontiers in Psychiatry, 2025)
BackgroundIt is well known that postmenopausal women have an increased risk of depression, and there is a dose correlation between carotenoid intake and depression. However, there is no clear study on the relationship between carotenoids and the risk of depression in postmenopausal women. To evaluate the relationship between the prevalence of depression and carotenoid intake in postmenopausal women.MethodsThe study was based on the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018 and included 1089 postmenopausal female participants. A logistic regression model was used to verify the relationship between carotenoid intake and the prevalence of depression in postmenopausal women. A restricted cubic spline (RCS) model was used to study the dose-response relationship between carotenoid intake and depression.ResultsAfter adjusting for confounding variables, Odds Ratios (95% confidence intervals) were found for depression in the highest quartile compared with the lower quartile. Among them, the results of lutein zeaxanthin and β-cryptoxanthin were not statistically significant (P > 0.05). Total lycopene 0.29 (0.10,0.87), β-carotene 0.41 (0.18,0.94), and total carotenoid 0.25 (0.09,0.67) were negatively correlated with the risk of depression in postmenopausal women. When α-carotene intake exceeded 2.90 mg/day, it was negatively and non-linearly associated with the prevalence of depression in postmenopausal women (P-nonlinear < 0.0022). When β-carotene intake exceeded 1.06 mg/day, it was negatively correlated with the prevalence of depression in postmenopausal women. It had an L-type nonlinear relationship with the prevalence of depression (P-nonlinear < 0.0016). Total lycopene was linearly correlated with the prevalence of depression in postmenopausal women (P-nonlinear = 0.3). When the intake exceeded 2.05 mg/day, it was negatively correlated with the prevalence.ConclusionThe study found that dietary intake of sufficient α-carotene, β-carotene, lycopene, total lutein, and zeaxanthin was negatively correlated with the prevalence of depression in postmenopausal women. Still, there was no dose correlation between β-cryptoxanthin.